INSTITUTIONAL MECHANISMS OF MODERNIZING THE FINANCIAL PROVISION SYSTEM IN HIGHER EDUCATIONAL INSTITUTIONS (Global Conference on Multidisciplinary Research and Innovation, 2026)
Modern higher education institutions operate in an increasingly complex environment, characterized by rapid technological change, growing student populations, and heightened expectations for academic quality and research output. In this context, the modernization of financial provision systems has become a critical priority for universities worldwide. Effective institutional mechanisms that support financial planning, resource allocation, and accountability are essential for ensuring sustainable development, operational efficiency, and competitiveness in the global higher education landscape.